PERSEPSI SISWA KELAS XI TERHADAP KOMPETENSI SOSIAL GURU SMK NEGERI 1 SOLOK - Azizatul Resti Husnia (Universitas Negeri Padang, 2015)
The goal of this article are to obtain information about the perception of a class XI student of the social competence of teachers of SMK Negeri 1 Solok. The population of this article class XI student, are 479 students and 91 students were taken as a sample. sampling technics were using is simple random sampling with slovin formula. The instrument used in this article is questionnaire and analyzed by average. In general, the results of this article is the perception of a class XI student of the social competence of teachers of SMK Negeri 1 Solok have good category at 3.69. Keyword: perception And social competence